Association between sperm DNA fragmentation index and recurrent pregnancy loss: results from 1485 participants undergoing fertility evaluation - Yao, Guanying; Dou, Xianchao; Chen, Xiaozhu; Qi, Haolin; Chen, Jianling; Wu, Peiwei; Li, Jialu; Liang, Shuang; Han, Zhongjiang; Bai, Shun; Hu, Xu (Frontiers in Endocrinology, 2025)
ObjectiveSeveral male factors have been reported to play a role in recurrent pregnancy loss (RPL). The aim of this study is to explore the relationship between semen parameters, sperm DNA fragmentation index (DFI) and RPL.MethodA total of 1485 participants were recruited from a university hospital between April 2020 and August 2022. Six hundred and thirtyfour men from couples with RPL were assigned to the case group, while 851 men from couple without RPL who underwent fertile evaluation were assigned to the control group. Semen parameters including sperm DNA fragmentation, were assessed. ResultsNo statistically significant differences in semen parameters, sperm kinematics and DFI were observed between the case group and the control group. A higher proportion of men in the case group had a DFI > 30% compared to those in the control group; however, this difference was not statistically significant. Restricted cubic spline analysis revealed no significant non-linear relationships between continuous DFI and risk of RPL.ConclusionOur study indicates that there is no significant relationship between DFI and RPL risk. Further prospective studies are needed to explore the impact of DFI on fertility outcomes in couples experiencing RPL.